CyberNotary Dalam Penyelenggaraan Sertifikasi Elektronik - Budi Agus Riswandi (Universitas Borneo Tarakan, 2020)
Abstract Technically there are five principles of an electronic transaction is declared safe, which contains the principle of authenticity, integrity, non repudation, writing and signature and confidenciality. In order to realize these five principles is legally set forth in the form of electronic certification. Electronic certifications are electronic certificates containing Electronic Signatures and identities that indicate the legal status of the parties in the Electronic Transactions issued by the Electronic Certification Operator. One of the institutions providing electronic certification is an electronic certification reliability institution. This institution is independent and filled by professionals, one of which is notary profession. From this comes the concept called cybernotary. This paper is intended to describe cybernotary degan based on the method of normative research conceptually derived data bibliography Keyword: CyberNotary, Sertificate, Law